AT2G21280 Only Has a Minor Role in Chloroplast Division - Li, Yiqiong; Wang, Lulu; Wang, Guangshuai; Feng, Yue; Liu, Xiaomin (Frontiers in Plant Science, 2017)
Chloroplast division is an important cellular process, which involves complicated coordination of multiple proteins. In mutant plants with chloroplast division defects, chloroplasts are usually found to be with enlarged size and reduced numbers. Previous studies have shown that AT2G21280, which was named as GC1 (GIANT CHLOROPLAST 1) or AtSulA, was an important chloroplast division gene, because either reduced expression or overexpression of the gene could result in an apparent chloroplast division phenotype (Maple et al., 2004; Raynaud et al., 2004). To further study the function of AT2G21280, we obtained mutants of this gene by CRISPR/Cas9-mediated gene editing and T-DNA insertion. Most of the chloroplasts in the mutants were similar to that of the wild type in size. Larger chloroplasts were rarely found in the mutants. Moreover, we obtained transgenic plants overexpressing AT2G21280, analyzed the chloroplast division phenotype, and found there were no significant differences between the wild type and various overexpressing plants. Phylogenetic analysis clearly indicated that AT2G21280 was not in the family of bacterial cell division protein SulA. Instead, BLAST analysis suggested that AT2G21280 is an NAD dependent epimerase/dehydratase family enzyme. Since the main results of the previous studies that AT2G21280 is an important chloroplast division gene cannot be confirmed by our intensive study and large chloroplasts are rarely found in the mutants, we think the previous names of AT2G21280 are inappropriate. Localization study results showed that AT2G21280 is a peripheral protein of the inner envelope of chloroplasts in the stroma side. AT2G21280 is well conserved in plants and cyanobacteria, suggesting its function is important, which can be revealed in the future study.